Problem-Based Learning: Upaya Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran PAI di SMA Negeri 1 Mlati - Retno Endah Sawitri (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
This research aims to improve the motivation of learning Islamic Religious Education subjects which refers to the application of problem-based learning models. This study uses a class action research method consisting of two cycles, including planning, implementation, observation, and reflection activities. The subject of the study was grade XI mipa-1 students of SMA Negeri 1 Mlati Year 2019/2020. Data on the implementation of the learning process by teachers is carried out through the observation sheet of the learning process, the data of the student's response process is carried out through the student's response questionnaire sheet, the student's learning motivation data is carried out through the student's motivational motivational observation sheet, while the data on changes in student learning motivation behavior is implemented through a questionnaire of changes in the motivational behavior of learning. The results showed that in cycle I, the implementation of the learning process, the student's response to the learning process, the motivation of the student's learning, and the changes in the motivation of the student's learning are in the category has not been successful. While in cycle II, the activity is in the category of success.